Genome-Wide identification and expression analysis of CsABF/AREB gene family in cucumber (Cucumis sativus L.) and in response to phytohormonal and abiotic stresses - Siting Lu; Yali Qiao; Xuejuan Pan; Xinfang Chen; Wanyi Su; Ailing Li; Xuelian Li; Weibiao Liao (Scientific Reports)
Abstract Abscisic acid (ABA)-responsive element binding factors (ABF)/ABA-responsive element binding proteins (AREB)/ABA insensitive protein 5 (ABI5) all belong to the basic leucine zipper (bZIP) transcription factor A subfamily. The bZIP transcription factor family contains 13 subfamilies, namely groups A, B, C, D, E, F, G, H, I, J, K, M and S, and the ABF/AREB/ABI5 gene belongs to A subfamily of the bZIP transcription factor. However, genomic analysis of CsABF/AREB in cucumber (Cucumis sativus L.) has not been systematically studied. In this study, we analyzed the characterization of CsABF/AREB family members and their response to phytohormonal and abiotic stresses. The results showed that a total of 8 genes family members were identified in cucumber. Structural domain analysis showed that the proteins of these family members are highly similar, and all of them belong to the bZIP structural domain. qRT-PCR analysis showed that CsABF/AREB members are expressed in root, stem, and leaf, with the highest expression in root, followed by stem and leaf. In addition, all 8 CsABF/AREB genes respond to ABA and methyl jasmonate (Me-JA). Among them, CsABF7 has the highest expression under both ABA and Me-JA treatments. Drought and salt stress significantly induce CsABF1, CsABF2, CsABF7, and CsABF8 expression. Drought and NaC1 stresses significantly induce the expression of CsABF1, CsABF2, CsABF7, and CsABF8. This study provides a basis for a further understanding of the role of CsABF/AREB homologous genes in response to abiotic stress and lays the foundation for further research on the function of CsABF/AREB.